The chronotope of O. E. Mandelshtam’s Poems about the Unknown Soldier - Shul’ts, Sergei (Slavica, 2024)
The chronotope of O.E. Mandelstam’s Poems about the Unknown Soldier has at least three levels: (1) the level of internal time-space as immanent to the subject, the author-hero; this is the level of subjective refraction of events in individual consciousness/thinking; (2) the level of external time-space: the historical and natural beginning of world life (historical and physical cosmos) in their correlation; here worldly life is presented as if outside any of its perception from the outside, “by itself”; and (3) the mythical-symbolic dimension shining through the other two; the events here are interpreted in their parabolical content, including in the aspect of the philosophy of culture and intertextuality as a kind of “new mythology”.